Design and analysis of HSC-BPPV diagnostic maneuver based on virtual simulation - Li, Yanjun; Yang, Xiaokai (Frontiers in Neurology, 2023)
Background The preferred supine roll test for the diagnosis of horizontal semicircular canal BPPV has several disadvantages, including difficulty in locating the affected ear, inconsistent nystagmus performance on repeated testing, and lack of a typical latency period, resulting in insensitive diagnosis. Objectives To investigate novel diagnostic techniques with more scientific design, more accessible application, and better diagnostic sensitivity and specificity. Materials and methods Based on clinical microscopic CT data, we created a virtual simulation model of BPPV using Unity software. The physical simulation of the traditional supine roll test was performed to observe and analyse the movement of the otoliths, whose initial position was the typical stable position. In addition, the normal vectors of the plane and crista ampullaris of the horizontal semicircular canal were measured using 3D Slicer software. Based on this, we analyzed the critical steps for designing diagnostic maneuvers for BPPV in the horizontal semicircular canal. For a more accurate diagnosis of horizontal semicircular canal BPPV, it is critical to rotate the horizontal semicircular canal to be parallel to gravity. It is also necessary to move the otolith by swinging the head. As a result, we developed two diagnostic maneuvers: the 60° roll test and the prone roll test. We also performed simulations to observe otolith movement and predict nystagmus performance. Conclusions The 60° roll test and the prone roll test can complement the supine roll test. Compared to the supine roll test, they not only effectively differentiate canalolithiasis from cupulolithiasis, but also make it easier to determine the position of the otoliths, and the characteristics of the nystagmus are more pronounced. Significant diagnostic features have significant potential benefits for home and telemedicine.